Preparation and photoelectric properties of nitrogen-doped graphene quantum dots modified SnO2 composites. (April 2022) - Lei, Yun; Wang, Yongqin; Du, Peng; Wu, Yuncui; Li, Can; Du, Beibei; Luo, Linhui; Sun, Zhengguang; Zou, Bingsuo
Abstract: Nitrogen-doped graphene quantum dots modified SnO2 composites (SnO2 /N-GQDs) were prepared by a solvothermal method, where N-GQDs were synthesized through a hydrothermal process with citric acid and urea as sources. The lattice stripes of 0.33 nm, 0.26 nm and 0.24 nm were ascribed to (110) and (101) crystal planes of SnO2 and (1120) crystal plane of N-GQDs, respectively. The photoelectric properties of SnO2 /N-GQDs composites with different N-GQDs contents were characterized using I-t, LSV, EIS, and Mott-Schottky. Among them, SnO2 /N-GQDs-2 composites reached the smallest electrochemical impedance and achieved the optimal transient photocurrent value of 1.880 × 10 −4 A/cm 2 . Compared with pure SnO2, SnO2 /N-GQDs-2 presented a 5-fold increase in the photocurrent density. LSV showed that the incorporation of N-GQDs could enhance the photocurrent intensity of SnO2 . The Mott-Schottky slope of SnO2 /N-GQDs-2 in light was smaller than that of SnO2 and SnO2 /N-GQDs-2 in dark, indicating that more carriers were generated under UV illumination and transferred with the doping of N-GQDs.